Acuan Pengembangan Media Pembelajaran Bahasa Indonesia Jenjang SMP Berbasis Filsafat Ilmu - Lukman Hakim; Anas Ahmadi (Jurnal Riset Multidisiplin Edukasi, 2026)
The focus of this study is how to develop Indonesian language learning media based on the philosophy of science. Learning media play an important role in improving the quality, effectiveness, and efficiency of learning by making materials easier to understand, increasing students’ motivation, and providing data, references, and concrete supporting tools (such as modules, media, human resources, and the environment) that support learning objectives. Teachers must ensure that the materials are relevant, engaging, and aligned with students’ goals and needs when developing learning media. However, some teachers face difficulties in creating learning media due to limited facilities and infrastructure, lack of creativity in relating materials to real-life contexts, or the mismatch between the media and students’ characteristics. Therefore, this study provides guidelines for the development of learning media using theoretical foundations from various philosophical perspectives, including philosophical, psychological, technological, empirical, theoretical, practical, and productive aspects. The purpose of this study is to assist teachers in developing learning media, and these guidelines can serve as a basis before creating learning media by first understanding students’ characteristics and classroom conditions. This study employs a qualitative descriptive method, with data collection techniques including literature review, observation, and interviews. When applied properly, this philosophy-based learning media development plan can support the creation of effective learning media.